Christological Laxity, Nicodemism, and Baptist Identity: A Reply to Stephen R. Holmes - Chandler, Kegan A. (2024)
Stephen R. Holmes has argued that all early General Baptists were both unreflectively orthodox in their trinitarianism and insistent on orthodox Christology as a non-negotiable part of the Christian faith, promoting a relatively tranquil image of Baptist Christology prior to the 1690s debates surrounding Matthew Caffyn (1628–1714). Additionally, he has argued that General Baptist non-negotiables included orthodox Christology even in the 1690s, with latitude allowed merely in the language involved. He has also treated the case of Matthew Caffyn and any potential tolerance of his unorthodoxy as basically not representative of the Baptist tradition. In this article, I offer a response through an examination of Baptist treatment of unorthodox Christology from the movement’s beginnings to 1730; subsequently, I offer a view of the unorthodox nature of Caffyn’s Christology and an explanation of his behaviour (and that of his peers) during his theological interrogations. While Holmes paints Caffyn as a bold controversialist who would never hide his views, I offer an alternative account based on the then-current English trend of Nicodemism. The article concludes with a brief revisitation of Baptist identity in light of the preceding history.
Keywords: Nicodemism; Christology; General Baptists; Matthew Caffyn